Pengaruh Komposisi Media Tanam Terhadap Perkecambahan Benih Cendana (Santalum album Linn.) - Gue, Yohanes; Seran, Wilhelmina; Sinaga, Pamona Silvia (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Sandalwood (Santalum album Linn.) is a wood-producing forest plant in the province of East Nusa Tenggara (NTT) which has great economic value and is an endemic species. The sandalwood (Santalum album Linn.) propagation has been widely carried out in NTT, various studies have been carried out to increase the sandalwood plant, with the development and replanting of sandalwood (Santalum album Linn.) plants from nurseries or saplings from natural distribution. Utilization of sawdust waste as a seedling medium is one method to support the development of sandalwood plants, the increase in sandalwood productivity depends on the fertility of the planting media. Sawdust waste contains chemical compounds such as lignin, cellulose, and hemicellulose. The method used in this study was Completely Randomized Design (CRD) with a comparison of the composition of the growing media used (A0) Soil (100% (control))10kg, (A1) 50% soil + 25% sawdust waste + 25% sand, (A2) 25% soil + 50% waste sawdust + 25% sand, (A3) 25% soil + 25% waste sawdust + 50% sand, (A4) 50% waste sawdust + 50% soil, (A5) 50% waste sawdust + 50% sand. The results of this study showed that the A3 treatment witha ratio of 25% soil + 25% sawdust waste + 50% sand gave the highest average increase and hada very significant effect on germination rate, germination rate index and germination value.